Socio-demographic factors facilitating intestinal helminth infestation and impact of single dose of mebendazole administration among the street children of Karwan Bazar, Tejgaon, Dhaka - Mukutmoni, Mandira; Khanum, Hamida (Asian Journal of Medical and Biological Research, 2018)
A total of eighty stool samples from forty street children living in Karwan Bazar, Tejgaon area were collected to study the prevalence of intestinal helminths during February 2017 to May 2017. The highest prevalence of Ascaris lumbricoides and Trichuiris trichiura was observed among the children aged 13-15 (70%) years old followed by the age group 7-9. Male children were more A. lumbricoides prevalent (53.57%) followed by T. trichiura (46.43%) than the female children (41.67%; for both the A. lumbricoides and T. trichiura). Except Enterobius vermicularis and hookworm, heavy infestation with other worms was reduced; esspecially A. lumbricoides (50% to 12.5%) and T. trichiura (45% to 15%), after administering Mebendazole (Vermox 500mg, single dose). Children who collected waste material from dustbin were highly helminth prevalent group (91.67%) followed by vegetable shop worker (66.67%). In February 2017, double infection showed the highest occurrence (32.5%). After administering single dose of mebendazole, in May 2017, single infection was at the peak (55%). With the initiation of broad-spectrum anthelminthic drugs that are low-priced, non-hazardous and simple to deliver, further control programs should include health education, public and good personal hygiene practices among the street children. Asian J. Med. Biol. Res. June 2018, 4(2): 172-177